PESANTREN’S DIGITAL LITERACY: An Effort to Realize the Advancement of Pesantren Education - Fadli, Muhammad Rijal; Dwiningrum, Siti Irene Astuti (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
There are still many digital literacy gaps among pesantren in Indonesia due to maintaining the pesantren culture itself. Pesantren must be able to adapt to the times in the digital era, so they can compete with other educational institutions by utilizing digital literacy. The purpose of this article is to analyze pesantren digital literacy skills as an effort to realize the progress of pesantren education. The method used is library research with descriptive analysis study. The data is analyzed using content analysis and descriptive studies related to digital literacy in pesantren by using data sources from previous studies. The results explain that digital literacy is an opportunity and potential for pesantren education to be developed so that the role of pesantren in society is more advanced and superior. So, pesantren remains adaptive to the developments and demands of the times as needed. The digital literacy can be in the form of critical, creativity, imagination, and creative thinking skills in understanding technological developments so that they can use them well. Pesantren digital literacy is optimized as a form of effort in realizing the progress of pesantren education in Indonesia.